EVALUATING PHYSICAL EDUCATION CURRICULUM FOR THE INTERMEDIATE STAGE AS PERCEIVED BY TEACHERS IN ANBAR GOVERNORATE - Al- leheeby, Muder Qahtan Hameed; Al-Oun, Ismael (European Scientific Journal, ESJ, 2014)
The purpose of this study is to evaluate physical education curriculum for the intermediate stage as perceived by teachers in Anbar governorate. Moreover, findings if there are any significant statistical differences attributed to gender, scientific qualification and experience. The population of the study consisted of (181) male and female teachers in public schools as Anbar governorate in (Al-rmadi, Hbanya, Fluja, Heet, Haditha, Rawa, Ana, Qae’m and rutba). The population was considered the sample of this study but the researcher retrieved (157) questioners with a rate of (86.7%). For the purposes of the study the researcher developed a questionnaire consisted of (60) items distributed into five domains: goals. Teaching planning, curriculum and content, teaching strategies, aids and assessment). After collecting and analyzing data the findings showed that the evaluating physical education curriculum for the intermediate stage as perceived by teachers in Anbar governorate came in an average level as assessment domain came first followed by curriculum and content then goals and teaching planning while aids came in the last rank with means of (3.80). (3.71). (3.58) (3.50). Moreover, there were no significant statistical differences attributed to gender, scientific qualification and experience in teacher’s evaluation of physical education curriculum.